LEGALITAS SMART CONTRACT DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH Hukum Ekonomi Syariah - Usman; Ahmad Sarwini (KASBANA, 2026)
Abstract The development of blockchain technology has given rise to the innovation of smart contracts, enabling the automatic execution of agreements without intermediaries. However, this raises issues regarding the validity of contracts from the perspective of Islamic economic law. This study aims to analyze the legality of smart contracts based on the principles of Islamic jurisprudence (fiqh muamalah) and assess their compliance with the pillars and conditions of contracts in Islamic law. The research method used is normative juridical with a conceptual and legislative approach, through a review of fiqh literature, fatwas from the National Council of Islamic Scholars (DSN-MUI), and regulations related to electronic transactions. The results indicate that smart contracts can, in principle, be categorized as valid contracts if they fulfill the elements of aqidain (the parties), ma'qud 'alaih (the object of the contract), and shighat (the consent and acceptance) in the form of electronic agreements, and are free from gharar, maisir, and riba (usury). However, the complexity of the code and the nature of automation have the potential to create uncertainty and unfairness in their implementation. In conclusion, smart contracts are acceptable under Islamic economic law, provided they are reconstructed based on the principles of transparency, fairness, and sharia oversight to ensure compliance with the maqasid (maqasid) of sharia, particularly in the protection of assets (hifz al-mal). Keywords: Smart Contract, Blockchain, Islamic Economic Law, Contract, Fiqh Muamalah, Maqasid Sharia